Extinction dynamics: The interplay of species traits and the spatial scales of metapopulation declines - Emma J. Walker; Benjamin Gilbert (Ecology, 2023)
Global changes can lead to species declines and extinctions through their impacts on species habitats at two distinct spatial scales: habitat destruction, in which individual habitat patches are destroyed by land‐use change or natural disasters, and habitat degradation, in which larger scale changes, such as nitrogen deposition or climate change, lower mean population abundances across landscapes. We developed a theory showing that, even when these two forms of global change have an identical impact on a species' total amount of habitat, they have qualitatively different consequences for species dynamics and extinction. Using metapopulation theory and simulations, we found distinct impacts of these global changes characterized through several responses: the rate at which populations are lost from the remaining patches, extinction thresholds, and the duration of extinction debts. Habitat degradation causes a faster decline in species populations when habitat reduction is low, making it particularly detrimental for rare species. Habitat destruction has smaller impacts for low habitat reduction, but shows clear thresholds beyond which it surpasses degradation's negative impact; the location and steepness of the threshold depends on species dispersal, with poor dispersers having steeper thresholds. These results highlight the challenge of using population monitoring to assess the consequences of global changes and predict consequences of further change: extinction trajectories cannot be predicted due to thresholds (habitat destruction) and lagged dynamics that lead to extinction debts (habitat degradation). Our research clarifies why the impacts of one type of global change may poorly predict the impacts of the other and suggests general rules for predicting the long‐term impacts of global changes based on species traits.